Science, food, and society: Charting out the future role of science policy in developing-country agriculture - Spielman, David J. (2016)
IFPRI Senior Research Fellow David Spielman’s presentation at the third Global Conference on Agricultural Research for Development (GCARD3). For more information, please visit: https://www.ifpri.org/event/third-global-conference-agricultural-research-development